Asthma related quality of life and health economics - Thomas, Mike (Prim Care Respir J, 2002)
In a time of limited health care resources, it is important for medical interventions to be cost effective as well as clinically effective. As one of the commonest chronic diseases in the community, the direct and indirect costs of asthma place a significant burden both on the individual and on the wider community. Primary care physicians are under increasing pressure to limit health costs, and to provide cost effective care. Direct prescribing costs may only account for a fraction of the total costs associated with asthma. As there are several alternative therapeutic options available in the treatment of asthma of all levels of severity, economic evaluations assessing the various direct and indirect costs of care are vital to allow informed decision making and efficient use of limited resources. It is important for primary care clinicians to have accurate information on the costs and benefits of the interventions they initiate, and on the relative cost effectiveness of different therapeutic options. Economic evaluations attempt to quantify the costs of disease and of disease management in relation to clinically relevant outcome measures. As there are now a number of different outcome measures for asthma care, including lung function, symptoms, exacerbations and health status, economic evaluations need to incorporate different outcome measures. There is increasing recognition of the importance of patient centred outcomes such as disease related quality of life in asthma. This paper surveys the current tools for assessing the clinical and economic outcomes of asthma care, with particular attention to quality of life, and reports on projects under development to produce, validate and implement tools to allow accurate economic evaluations of asthma treatments.